Corporate Social Responsibility dan Kinerja Keuangan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Drianita, Alifia Nur; Hasibuan, Henny Triyana (E-Jurnal Akuntansi, 2021)
For a company that is increasingly developing, the level of exploitation of natural resources and its social community will certainly be higher and uncontrollable, therefore there is awareness from the company to implement corporate social responsibility (CSR). This study aims to determine the effect of CSR on financial performance with company size as a moderating variable. This research was conducted in mining sector companies listed on the IDX for the 2017-2019 period. The sampling method used was non-probability sampling with purposive sampling technique, where the results were a sample of 22 companies. Moderated regression analysis was used to analyze the data of this study. The results showed that CSR has a significant positive effect on financial performance, and company size can moderate the effect of CSR on financial performance. Keywords: Corporate Social Responsibility; Financial Performence; Company Size.